2019
DOI: 10.5267/j.msl.2019.7.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the application of management accounting in small and medium enterprises in Hanoi, Vietnam

Abstract: This article evaluates the factors affecting the use of management accounting in small and medium enterprises (SMEs) in Hanoi, Vietnam. The factors include: Production and business characteristics; Competitiveness; Business strategy; CEO of awareness management; Human resource quality. The study is conducted on 238 SMEs in Hanoi and the results show that CEO's awareness of management accounting had the strongest impact on the ability to apply management accounting of enterprises while competition level factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(30 reference statements)
1
16
0
Order By: Relevance
“… Nguyen and Nguyen (2000) reported the presence of H. microdoratus from a forest in Gia Lai, Vietnam. The female of Vietnamese population of H. microdoratus is characterized by having lip region not offset from body contour, bearing two annuli, first annulus larger than second; labial disc slightly elevated, rounded; cuticular annuli 3 to 5 µm wide at mid-body; stylet knob anchor-shaped, 5 to 6 µm long; dorsal orifice gland located 3 to 5 µm posterior to stylet base; secretory-excretory pore located 97 to 105 µm from anterior end; vulva located 11 annuli anterior to tail end, vulvar sheath present; anus located 1 annulus posterior to vulva; and tail tapering to a rounded tail tip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Nguyen and Nguyen (2000) reported the presence of H. microdoratus from a forest in Gia Lai, Vietnam. The female of Vietnamese population of H. microdoratus is characterized by having lip region not offset from body contour, bearing two annuli, first annulus larger than second; labial disc slightly elevated, rounded; cuticular annuli 3 to 5 µm wide at mid-body; stylet knob anchor-shaped, 5 to 6 µm long; dorsal orifice gland located 3 to 5 µm posterior to stylet base; secretory-excretory pore located 97 to 105 µm from anterior end; vulva located 11 annuli anterior to tail end, vulvar sheath present; anus located 1 annulus posterior to vulva; and tail tapering to a rounded tail tip.…”
Section: Resultsmentioning
confidence: 99%
“…The sheathoid nematodes, Hemicriconemoides (Chitwood and Birchfield, 1957), are root-ectoparasitic nematodes that cause damage to various crops ( Sikora et al, 2018 ) with 54 valid species worldwide ( Maria et al, 2018 ). In Vietnam, five Hemicriconemoides species have been reported including H. litchi (Misra and Edward, 1963), H. mangiferae (Siddiqi, 1961), H. cocophilus ( Loos, 1949 ; Chitwood and Birchfield, 1957), H. microdoratus ( Dasgupta et al, 1969) , and H. brachyurus ( Loos, 1949 ; Chitwood and Birchfield, 1957; Dasgupta et al, 1969 ; Nguyen and Nguyen, 2000 ). However, to the best of our knowledge, molecular data of Hemicriconemoides spp.…”
mentioning
confidence: 99%
“…Twenty-one species of the Meloidogyne genus have been recorded on coffee (Souza, 2008; Humphreys-Pereira et al ., 2014). In Vietnam, only M. incognita, M. exigua and M. coffeicola have been recorded on coffee (Trinh et al ., 2013), and M. incognita causes serious damage at almost all the coffee areas (Nguyen & Nguyen, 2000, 2001; Trinh et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For small and medium-sized enterprises, the application of management accounting and the factors affecting the application of management accounting in these enterprises have received attention from researchers. Nguyen et al (2019) found that CEO's perception of management accounting has a positive impact on the application of management accounting in small and medium-sized enterprises in Hanoi (Vietnam), while the age of managers has a negative impact on the application of management accounting and competition has the weakest impact. Le et al (2019) examined 120 Vietnamese enterprises in the fields of manufacturing, trading and services to investigate factors affecting the application of management accounting in enterprises in this field.…”
Section: Review Of Studies On the Application Of Management Accountingmentioning
confidence: 99%